Retrofitting internal combustion engine motorbike into electric motorbike - Mohd Rajmin Affendi bin Abdullah (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
The existence of Electric Vehicles (EV) such as electric cars, buses and trams, has gained its prominence since these past few decades, primarily contributed by the environmental and economic factors. It is until recently that the automotive market shifted into the production of electric motorbikes. One criteria that stands out about the electric motorbikes as compared to others is the instantaneous power delivered by the motor. However, the implementation of electric motorbike requires that it has to be built from scratch, which in turn, defeats the cost-saving purposes. Therefore, the aim of this research is to retrofit a commercial motorbike into an electric motorbike by replacing the fuel storage and internal combustion engine with batteries and a Direct Current (DC) motor. A Honda Cross Beam Racer (CBR) 250cc motorbike has been used for this study. We scanned the frame of the motorbike using a special three-dimensional (3D) scanner machine to obtain its accurate dimensions. The battery and motor housings were then designed based on the acquired dimensions, and static analysis was later conducted to estimate their strengths. The motor and battery housings were then fabricated and tested on the motorbike. Result shows that steel alloy material is more suitable to be used as the battery housing and the DC motor holder. Static and dynamic analyses were done on three different designs for battery housing and two different designs on motor holder. The identified optimum motor holder and battery housing combination was the ones that were capable to withstand loads up to 26 kN. Retrofitted E-Bike Design 1 has a different of 15.7% of the Center of Gravity (COG) compare to the original Honda CBR 250. The Design 2 has 41.44% difference of the COG compare to the original motorbike. Retrofitted E-bike Design 3 show the lowest changed in COG compare to original motorbike with 8.91% difference. The outcome of this research work provides an optimistic possibility that commercial motorbikes can be retrofitted into electric bikes without compromising their original performances. This in turn will hopefully encourage more commercial motorbike users to retrofit theirs into electric motorbikes that are economic and environmental friendly.